Circulating Interleukin-23 Levels in Rheumatoid Arthritis and its Relationship to Disease Activity: a Systematic Review with Meta-Analysis - Azzam, Ahmed; Abdul Basset Abdul Basset, Shaza; Khaled, Heba; Refaey, Neveen; Atta Ahmed Ali, Ahmed; abdelrahim saad shoulah, Saad; Saleh Al Saifi, Mohammed; s.Meleha, Mahmoud (AL-Kindy College Medical Journal, 2023)
Background: Rheumatoid arthritis (RA) is a chronic and systemic autoimmune disease that is characterized by severe synovial inflammation, cartilage erosion, bone loss, and generalized vasculopathy. Although the immunologic mechanism of RA is still unclear, it is now thought to be a primarily Th17-driven disease. Along with other factors, IL-23 stimulates the expansion of Th17 cells from naive CD4+ T cells. Objective: The objective of this study is to assess the circulating levels of interleukin (IL)-23 in rheumatoid arthritis (RA) and determine the correlation between plasma/serum IL-23 levels and disease activity. So, we performed a systematic review with meta-analysis comparing plasma/serum IL-23 levels between patients with RA and controls and examined correlation coefficients between circulating IL-23 levels and disease activity Subjects and Methods: Using the following keywords: lenterleukin-23, IL-23, and rheumatoid arthritis, a comprehensive literature search was carried out in the following databases: PubMed, Scopus, Google Scholar, and Web of Science. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses standards were followed, and the review was registered in the PROSPERO International prospective register of systematic reviews with registration number CRD42022345901. Results were reported as standardized mean differences (SMDs) with a 95% confidence interval. All statistical analysis was performed using StatsDirect statistical software version 3.0.0 (StatsDirect Ltd., Cheshire, UK). A sensitivity analysis was conducted using the leave-one-out approach to test the robustness of the results. Results: The total sample size for the RA group included in our review was 408 cases, while the control group sample size was 244 cases. The serum IL-23 level in the RA group was significantly higher than the control group (pooled SMD = 3.5, 95% CI; 2.1: 4.8, P < 0.0001) as compared to the control group. There were 8 studies with a total sample size of 402 that reported the correlation between IL-23 and DAS28-based RA activity. According to our findings, a significantly positive correlation between IL-23 and DAS28-based RA activity was found, with a weighted mean correlation of 0.57 (95% CI; 0.4: 0.75, P < 0.0001). Conclusion: Our meta-analysis has shown that IL-23 circulatory levels are higher in RA patients and that there is a significant positive correlation between IL-23 and disease activity. Our findings emphasize the role that IL-23 may have in RA. More studies may be required to fully comprehend the involvement of IL-23 in RA.